2014
DOI: 10.5194/bg-11-1361-2014
|View full text |Cite
|
Sign up to set email alerts
|

Relative roles of local disturbance, current climate and paleoclimate in determining phylogenetic and functional diversity in Chinese forests

Abstract: Abstract. The main processes underlying the generation and maintenance of biodiversity include both local factors such as competition and abiotic filtering and regional forces such as paleoclimate, speciation and dispersal. While the effects of regional and local drivers on species diversity are increasingly studied, their relative importance for other aspects of diversity, notably phylogenetic and functional diversity is so far little studied. Here, we link data from large Chinese forest plots to data on curr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 56 publications
5
41
0
Order By: Relevance
“…Sandel et al (2011) showed that high climatechange velocity since the Last Glacial Maximum is responsible for the global absence of endemism (e.g., amphibians, mammals, and birds). Variation between the Last Glacial Maximum (LGM) and the current climate has also had a high impact on the phylogenetic diversity structure of Chinese woody community lineage (Feng et al, 2014). Kissling et al (2012) The typical desert area in this study belongs to the ancient Tethys region (Zhu et al, 1999) and has experienced a relatively stable arid climate since the late Tertiary (Liu, 1995).…”
Section: Effect Of Paleoclimate and Geological History On Phylogenementioning
confidence: 99%
“…Sandel et al (2011) showed that high climatechange velocity since the Last Glacial Maximum is responsible for the global absence of endemism (e.g., amphibians, mammals, and birds). Variation between the Last Glacial Maximum (LGM) and the current climate has also had a high impact on the phylogenetic diversity structure of Chinese woody community lineage (Feng et al, 2014). Kissling et al (2012) The typical desert area in this study belongs to the ancient Tethys region (Zhu et al, 1999) and has experienced a relatively stable arid climate since the late Tertiary (Liu, 1995).…”
Section: Effect Of Paleoclimate and Geological History On Phylogenementioning
confidence: 99%
“…This is understandable as the absence of a species in a particular habitat can either be owing to it was not dispersed there or because the environmental conditions were unsuitable for it to survive despite it had reached the habitat (Heino et al, ). Besides, some processes related to historical factors may also strongly structure regional species pool and thus influence species diversity within localities (Feng et al, ). Functional diversity should be most strongly determined by environmental variables owing to the close association between functional traits and environmental conditions (Ding et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic diversity, which is often linked to functional diversity through conserved traits, has likewise been shown to respond to climatic gradients in space and time (Potter and Woodall , Feng et al. , Eiserhardt et al. ).…”
Section: Introductionmentioning
confidence: 99%